2018
DOI: 10.4149/neo_2018_161217n648
|View full text |Cite
|
Sign up to set email alerts
|

An extensive study of the mechanism of prostate cancer metastasis

Abstract: The study aimed to identify the pivotal genes and pathways involved in prostate cancer metastasis. Using the expression profile dataset GSE7930, downloaded from the Gene Expression Omnibus (GEO) database, differentially expressed genes (DEGs) between primary and highly metastatic prostate cell samples were screened, followed by functional analysis and tumor associated genes (TAG) screening. Protein-protein interaction (PPI) network of DEGs was constructed and module analysis was performed. The expression of DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, the upregulated genes of macrophages with FABP4 overexpression was significantly enriched in the ECMreceptor interaction pathway (Figure S4A), which plays a role in cell-substrate junction and has been reported closely related to cancer metastases. 27 Moreover, RNA sequencing and flow analysis results showed that FABP4 knockdown in macrophages increased the expressions of CD80 and CCR7 (pro-inflammatory macrophage marker), but decreased the expressions of CD209 and CD36 (anti-inflammatory macrophage marker), which were all widely expressed on the surface of macrophages. Conversely, FABP4 overexpression exerted the opposite effects (Figure S4C).…”
Section: Fabp4-mediated Macrophages Promote Secretion Of Il1αmentioning
confidence: 97%
“…However, the upregulated genes of macrophages with FABP4 overexpression was significantly enriched in the ECMreceptor interaction pathway (Figure S4A), which plays a role in cell-substrate junction and has been reported closely related to cancer metastases. 27 Moreover, RNA sequencing and flow analysis results showed that FABP4 knockdown in macrophages increased the expressions of CD80 and CCR7 (pro-inflammatory macrophage marker), but decreased the expressions of CD209 and CD36 (anti-inflammatory macrophage marker), which were all widely expressed on the surface of macrophages. Conversely, FABP4 overexpression exerted the opposite effects (Figure S4C).…”
Section: Fabp4-mediated Macrophages Promote Secretion Of Il1αmentioning
confidence: 97%
“…Consistent with previous studies, most of the DEGs (such as IGFBP3 [ 19 ], ITGB3 [ 21 ], ZEB1 [ 22 ], GJA1 [ 23 ], MMP14 [ 24 ], GLI2 [ 25 ], AREG [ 26 ], LCN2 [ 27 ], MACC1 [ 28 ], GALNT3 [ 29 ] and NCOA1 [ 30 ]) were involved in a wide spectrum of processes in tumorigenesis and tumor progression, such as the self-renewal of cancer stem cell, the invasion and metastasis. Interestingly, many of these DEGs (such as IGFBP3 [ 31 ], ITGB3 [ 32 ], ZEB1 [ 33 ], GJA1 [ 34 ], MMP14 [ 35 ], GLI2 [ 36 ] and NCOA1 [ 37 ]) were previously reported to contribute to PCa progression. It is worth noting that certain genes (such as IGFBP3 [ 38 ], GJA1 [ 39 ]) have been implicated in docetaxel treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…COL6A1, COL6A2, COL6A3, COL5A2, and COL11A1 are members of the collagen family, and these five genes are enriched in the pathway of “ECM–receptor interaction”, which leads to a direct or indirect control of cellular activities such as adhesion, migration, differentiation, proliferation, and apoptosis. Accumulating evidence indicated that the “ECM–receptor interaction” pathway served as a critical role in the carcinogenesis and metastasis of human cancers, such as prostate cancer, 33 breast cancer, 34 and colorectal cancer. 35 In this study, we also screened “ECM–receptor interaction” as an important pathway by module analysis, which indicated the potential role in the pathogenesis of BCC.…”
Section: Discussionmentioning
confidence: 99%